Tailoring the Mechanical Properties of Metaluminous Aluminosilicate Glasses by Phosphate Incorporation - Grammes, Thilo; Limbach, René; Bruns, Sebastian; van Wüllen, Leo; de Ligny, Dominique; Kamitsos, Efstratios I.; Durst, Karsten; Wondraczek, Lothar; Brauer, Delia S. (Frontiers in Materials, 2020)
The characterisation of aluminosilicate glasses is highly relevant in geosciences and for engineering applications such as reinforcement fibres or touchscreen covers. The incorporation of phosphate as a third network-forming species into these glasses offers unique opportunities for fine-tuning glass properties via changes in glass structure and polymerisation. In this work, we studied melt-quenched aluminosilicate glasses within the system SiO2-Al2O3-Na2O-P2O5 with 50 to 70 mol% SiO2 and up to 7.5 mol% P2O5. All glasses were metaluminous (Al:Na = 1) in order to maximise the degree of polymerisation. Increasing the phosphate content at the expense of NaAlO2 lead to reduced glass polymerisation and density, resulting in a decrease in elastic moduli and hardness and an increase in strain-rate sensitivity. When increasing the silica content by substituting SiO4 for AlO4 tetrahedra, network polymerisation remained mostly unchanged, as confirmed by nearly constant molar volume and hardness. Densification upon indentation was analysed by Raman spectroscopy and finite element analysis. We find that the elastic properties and hardness of metaluminous phospho-aluminosilicate glasses are governed by changes in density and network polymerisation. Other mechanical properties underlie more complex changes in glass structure.